2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32831
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Transfer Student Success in an Engineering Baccalaureate Program

Abstract: The primary area of her work is evaluating STEM education projects that focus on opportunities for, and retention of, K-20 students in STEM areas, majors and fields. She also conducts education research focusing on questions about professional development for educators and how educators support student learning in STEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is reported that transfer students often experience difficulty feeling part of the student community and this can negatively impact their future academic achievements [3]. UTSA, like many 4-year university engineering programs work with local community colleges to create a detailed semester-by-semester course plans for eventual transfer [4], some social and academic integration activities [5] as well as cohort activities for transfer students [6]. Studies often associate the grades earned in foundational Calculus and Physics classes to be linked with the level of preparation for subsequent engineering courses.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that transfer students often experience difficulty feeling part of the student community and this can negatively impact their future academic achievements [3]. UTSA, like many 4-year university engineering programs work with local community colleges to create a detailed semester-by-semester course plans for eventual transfer [4], some social and academic integration activities [5] as well as cohort activities for transfer students [6]. Studies often associate the grades earned in foundational Calculus and Physics classes to be linked with the level of preparation for subsequent engineering courses.…”
Section: Introductionmentioning
confidence: 99%